2022
DOI: 10.1101/2022.10.31.514636
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

mRNA bivalent booster enhances neutralization against BA.2.75.2 and BQ.1.1

Abstract: The emergence of the highly divergent SARS-CoV-2 Omicron variant has jeopardized the efficacy of vaccines based on the ancestral spike. The bivalent COVID-19 mRNA booster vaccine within the United States is comprised of the ancestral and the Omicron BA.5 spike. Since its approval and distribution, additional Omicron subvariants have been identified with key mutations within the spike protein receptor binding domain that are predicted to escape vaccine sera. Of particular concern is the R346T mutation which has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 6 publications
1
34
0
Order By: Relevance
“…Preliminary preprints using lentiviral pseudotypes indicated that BA.5, BA.4.6 or BA.2.75 titers were comparable after monovalent or BA.5 bivalent boosters 25,27 . In contrast, when using tests based on recombinant SARS-CoV-2 infectious virus carrying spikes from different Omicron sublineages, it was observed that bivalent mRNA booster may broaden humoral immunity 26 . These discrepancies may be due to differences in experimental systems, the delay between booster administration and blood sampling and/or variation in immune imprinting across cohorts.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Preliminary preprints using lentiviral pseudotypes indicated that BA.5, BA.4.6 or BA.2.75 titers were comparable after monovalent or BA.5 bivalent boosters 25,27 . In contrast, when using tests based on recombinant SARS-CoV-2 infectious virus carrying spikes from different Omicron sublineages, it was observed that bivalent mRNA booster may broaden humoral immunity 26 . These discrepancies may be due to differences in experimental systems, the delay between booster administration and blood sampling and/or variation in immune imprinting across cohorts.…”
Section: Discussionmentioning
confidence: 94%
“…A few recent articles and preprints reported an extensive escape of these Omicron subvariants to neutralization, studying sera from individuals who received three or four vaccine doses, including a bivalent booster 25 26 17,27 . Most of these studies were performed with lentiviral or VSV pseudotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Among Omicron variants, the association was strongly attenuated ( Figure 5 ), consistent with Omicron’s resistance to vaccine-elicited neutralizing antibodies, which are a key aspect of protection from infection. 7,8,11 The ability of bivalent vaccines to offer additional protection against Omicron-related infections is still being resolved, 29,30 and the neutralizing antibody sensitivity of emergent variants may impact the ability of vaccine boosters to slow transition times to new variants going forward.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, new Omicron BA.2- and BA.4/BA.5-descendent sublineages (e.g., BA.4.6, BA.2.75.2, BQ.1.1, and XBB.1) have emerged (https://covid.cdc.gov/covid-data-tracker/#variant-proportions). Although early epidemiological data suggest these new sublineages have not shown signs of increased disease severity, they have accumulated additional spike mutations that could further evade vaccine- and/or infection-elicited antibody neutralization 24 . Here we compared the neutralization activities against these Omicron sublineages after a 4 th dose (following three doses of BNT162b2) of either the original monovalent BNT162b2 or the bivalent BA.4/5 booster in humans.…”
Section: Main Textmentioning
confidence: 99%
“…Although early epidemiological data suggest these new sublineages have not shown signs of increased disease severity, they have accumulated additional spike mutations that could further evade vaccine-and/or infection-elicited antibody neutralization [2][3][4] . Here we compared the neutralization activities against these Omicron sublineages after a 4 th dose (following three doses of BNT162b2) of either the original monovalent BNT162b2 or the bivalent BA.…”
mentioning
confidence: 99%